Pictures from the scene in the Yemeni narrative discourse contemporary (Journal of the College of Basic Education, 2023)
The living reality of the human being was not fully consistent with the aspirations of the great beings; lostThe struggle for survival between man and his surroundings has intensified since his formative dispersal over the globe. .It is natural for a person to look for ways to liberate himself from perpetuating fear in himself. soHis self-image worsened until it turned into a psycho-social disease that dominated the folds of perceptions.